Optimal Energy Production In The Yeşilirmak River Basin - Mücahit Opan; Efsun Bacaksız (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Optimal planning and operation of water resources aredepend on a complex structure and process that include country economics andlife standards. Currently, sustainable use and development of water resourcesto maximize possible benefits are the two big challenges to be overcome andefficient use of hydro power forms a significant component of this. In thisstudy, a water resources system with multi-objectives and multiple reservoirsis described. It is considered to three scenarios in this system. The system isset up on the optimal operation model for the long term planning. The techniqueof the dynamic programming with successive approximations is used forthe model. Objectivefunction in the optimization model has two stage, maximization of firm andtotal energies. The model is applied to a water resources system withmulti-objective and multiple reservoirs presented successively on the main andsecondary line of the Yeşilırmak River in the Yeşilırmak River Basin. Results obtained are evaluated tothe maximization of the energy production. Accordingly, the firm energyobtained from the optimal operational model for long term planning is presentedapproximate the value determined by empiric equations, and also the averageenergy in the model is % 32 better than the value determined by empiricequations. It is observed that the optimization process of the reservoirs withthe highest operational storage was controlled and managed.